Russian intelligence files on Asia. (Leiden, The Netherlands)
1 mikrofilm makarası (564 poz)
Keywords: General intelligence on the Persian army and the domestic political situation in the country. Geographical, topographical, statistical, ethnographical and hydrographical intelligence on Persia: Geographical and topographical intelligence: Maps and descriptions of Persia as a whole.